Analysis of Working Capital Turnover, Company Size, and Profitability at PT. Maxis Paragon, Gunungsitoli City, Years 2019-2022 - Hulu, Yolan Selviana; Buulolo, Nanny Artatina; Batee, Maria Magdalena; Harefa, Idarni (ProBisnis : Jurnal Manajemen, 2024)
The study aims to analyze working capital turnover, company size, and profitability at PT Maxis Paragon in Gunungsitoli City from 2019 to 2022. It's a descriptive study using secondary data, focusing on the company's financial reports. The findings indicate a healthy working capital turnover, exceeding the standard of >1 time. PT Maxis Paragon falls into the medium-sized enterprise category, with net worth ranging from Rp. 500 million to Rp. 10 billion and annual sales from Rp. 2.5 billion to Rp. 50 billion. However, profitability, measured by Return on Assets (ROA), shows substandard performance (<5.98%). Return on Equity (ROE) was below standard (<8.32%) for 2019-2020 but improved above standard for 2021-2022. Net Profit Margin (NPM) also indicates below-standard performance (<3.92%). These results suggest areas for improvement in profitability despite healthy working capital turnover and medium-sized enterprise status.